The English Learning Model Through Physical Activities - Feri Hidayat; Lestari, Hikmah; Widya Handayani (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to develop "English learning models through physical activities for elementary school children." This study is a development study by adopting the theory of Borg and Gall and its implementation up to the fourth stage. The results of the study indicate that the development of English learning models through physical activities has four models, namely sing lomhop, sing lewhop, sing lemhop and sing sunhop. The models that were declared feasible by 3 experts, namely learning experts, English material experts, and media experts were only two learning models, namely sing lomhop and sing lewhop. Furthermore, this model was applied to a small group trial at SDN 05 Sekayu City by researchers and observers and was declared applicable.